A Practical, Ligand-Free, Palladium-Catalyzed Isocyanide Insertion Reaction for the Construction of Novel Ring-Fused Quinazolinones - Ji, Fei; Lv, Mei-fang; Yi, Wen-bin; Cai, Chun (Synthesis, 2013)
A high-yielding, ligand-free, palladium-catalyzed isocyanide insertion reaction for the synthesis of phthalazino[1,2-b]quinazolinones from the readily obtainable quinazolinones has been developed. Easily handled and relatively low-cost palladium(II) acetate was used as the catalyst, without an additional ligand. Preparation of the quinazolinones involved the cascade reaction of isatoic anhydrides, phenylhydrazines and 2-bromobenzaldehyde catalyzed by p-toluenesulfonic acid in one pot. This novel protocol may be applicable for the synthesis of other important ring-fused heterocyclic compounds.
Keywords: ligand-free; palladium catalysis; isocyanide insertion reaction; ring-fused quinazolinones; depropargylation